Out of the Pacific: A New Alvinellid Worm (Annelida: Terebellida) From the Northern Indian Ocean Hydrothermal Vents - Han, Yuru; Zhang, Dongsheng; Wang, Chunsheng; Zhou, Yadong (Frontiers in Marine Science, 2021)
Alvinellids have long been considered to be endemic to Pacific vents until recent discovery of their presence in the Indian Ocean. Here, a new alvinellid is characterized and formally named from recently discovered vents, Wocan, and Daxi, in the northern Indian Ocean. Both morphological and molecular evidences support its placement in the genus Paralvinella, representing the first characterized alvinellid species out of the Pacific. The new species, formally described as Paralvinella mira n. sp. herein, is morphologically most similar to Paralvinella hessleri from the northwest Pacific, but the two species differ in three aspects: (1), the first three chaetigers are not fused in P. mira n. sp., whereas fused in P. hessleri; (2), paired buccal tentacles short and pointed in P. mira but large and strongly pointed in P. hessleri; (3), numerous slender oral tentacles ungrouped in P. mira but two groups in P. hessleri. Phylogenetic inference using the concatenated alignments of the cytochrome c oxidase I (COI), 16S rRNA and 18S rRNA genes strongly supports the clustering of P. mira with two West Pacific congeners, P. hessleri and an undescribed species (Paralvinella sp. ZMBN). The resulting Indian/West Pacific lineage suggests a possible invasion into the Indian Ocean from the West Pacific. This is the third polychaete reported from Wocan hydrothermal field. Among the three species, two including P. mira and Hesiolyra heteropoda (Annelida:Hesionidae) are present in high abundance, forming an alvinellids/hesionids-dominated polychaete assemblage distinct from that at all other Central Indian Ridge and Southwest Indian Ridge vents. Thus, this study expands our understanding of alvinellid biogeography beyond the Pacific, and adds to the unique biodiversity of the northern Indian Ocean vents, with implications for biogeographic subdivision across the Indian Ocean ridges.